2016
DOI: 10.1038/ejcn.2016.248
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of inulin and resistant starch on postprandial serum short-chain fatty acids and second-meal glycemic response in lean and overweight humans

Abstract: Background/ObjectivesColonic-fermentation of dietary-fibre to short-chain fatty-acids (SCFA) may protect against obesity and diabetes, but excess production of colonic SCFA has been implicated in the promotion of obesity. We aimed to compare the effects of two fermentable-fibres on postprandial SCFA and second-meal glycaemic response in healthy overweight or obese (OWO) vs lean (LN) participants.Methodsusing a randomized cross-over design, 13 OWO and 12 LN overnight fasted participants were studied for 6h on 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 47 publications
(57 reference statements)
3
49
1
1
Order By: Relevance
“…It has been estimated that 36% of colonic‐derived acetate becomes systemically available, in contrast to only 9% of propionate and 2% of butyrate . In healthy subjects, fasting levels of acetate in peripheral blood have been reported to rise from a mean of 54 to 169 μmol/L, 6‐8 h after consumption of a 24‐h high resistant starch diet, although this rise of >100 μmol/L has not been achieved through the use of inulin, guar gum or XOS fibre supplements . Circulating concentrations of SCFA levels are likely to be tightly controlled by energy levels within the body, as SCFA are known substrates for the production of glucose, fatty acids and ketone bodies, outlined in Figure .…”
Section: Pharmacokinetics Of Scfamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been estimated that 36% of colonic‐derived acetate becomes systemically available, in contrast to only 9% of propionate and 2% of butyrate . In healthy subjects, fasting levels of acetate in peripheral blood have been reported to rise from a mean of 54 to 169 μmol/L, 6‐8 h after consumption of a 24‐h high resistant starch diet, although this rise of >100 μmol/L has not been achieved through the use of inulin, guar gum or XOS fibre supplements . Circulating concentrations of SCFA levels are likely to be tightly controlled by energy levels within the body, as SCFA are known substrates for the production of glucose, fatty acids and ketone bodies, outlined in Figure .…”
Section: Pharmacokinetics Of Scfamentioning
confidence: 99%
“…Highly fermentable fibres, such as inulin and guar gum can produce a significant rise in plasma SCFA levels within 6 h when consumed as a 20‐30 g supplement . Furthermore, longer term consumption in studies ranging from days to weeks, of a similar dose of resistant starch increases faecal levels of total SCFA and butyrate .…”
Section: Utilising Scfa As a Therapeutic For Inflammatory Diseasementioning
confidence: 99%
“…35 Recent research showed that butyrate could regulate the release of GLP-1 through its central and peripheral targets. 32,34,36 However, Castillo et al reported that consumption of native banana starch supplementation (24 g/d) as a rich source ofRS2 for 4 weeks did not affect the lipid profile, HbA1c and FBS and insulin resistance in obeseT2DM patients. 37 Therefore, it is meaningful to investigate the effect of RS on blood lipids to obtain relatively reliable evidence.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…25 From the previous studies, RS played a useful role in health by some potential mechanisms include: ① changes in intestinal microbiota, ② a reduction in insulin, ③ resistance rise in HDL-c concentrations, and ④ an increase in SCFAs production. [3][4][5][6][26][27][28][29][30][31][32][33][34] RS could produce SCFAs through two pathways: directly (RS fermentation) or indirectly (increasing colonic butyrate-producing microbiota such as Lachnospiraceae and Ruminococcaceae). Butyrate can control macrophage activity and expression of NF-κB which is the main inflammatory and immune response.…”
Section: Summary Of Evidencementioning
confidence: 99%
See 1 more Smart Citation